Clinical Efficacy of Bone Marrow Aspirate Concentrate Versus Stromal Vascular Fraction Injection in Patients With Knee Osteoarthritis: A Systematic Review and Meta-analysis. Issue 5 (April 2022) - Bolia, Ioanna K.; Bougioukli, Sofia; Hill, William J.; Trasolini, Nicholas A.; Petrigliano, Frank A.; Lieberman, Jay R.; Weber, Alexander E.
Background: Knee injection using either bone marrow aspirate concentrate (BMAC) or stromal vascular fraction (SVF) from adipose tissue has been shown to result in symptomatic improvement in patients with knee osteoarthritis (OA). It is still unclear whether one of these therapies is superior over the other. Purpose: To systematically report the clinical studies evaluating BMAC and SVF in the treatment of knee OA and to compare the clinical efficacy of these 2 injection therapies. Study Design: Meta-analysis; Level of evidence, 4. Methods: This meta-analysis was performed per the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Studies were included if they reported the clinical outcomes after a single BMAC or SVF injection in the knee joint of patients with OA. Studies evaluating preparations of culture-expanded stem cells were excluded. A random effects model was used; the clinical efficacy of BMAC or SVF injection was assessed using the standardized mean difference (SMD) and compared. Visual analog scale (VAS) scores for pain and Western Ontario and McMaster Universities Osteoarthritis (WOMAC) knee index were the primary outcomes. The level of statistical significance was set at P < .05. Results: Ten studies and 472 patients with knee OA who received either BMAC (233 patients) or SVF (239 patients) were included. Patients who received an injection had improved VAS outcomes (mean ± SD): from 5.8 ± 1.3 to 2.6 ± 17 for BMAC and from 6.4 ± 1.4 to 3.4 ± 0.5 for SVF. They also experienced significantly reduced pain (SMD [VAS], 2.6 for BMAC and 3.4 for SVF) and improved function (SMD [WOMAC], 1.4 for BMAC and 1.2 for SVF). However, the SVF injection had a significantly greater effect on pain reduction than did the BMAC injection ( P < .0001). Based on WOMAC, the clinical effect of BMAC versus SVF knee injection in patients with knee OA was equivalent ( P = .626). Results were limited by the presence of publication bias as well as variability in the preparation methods utilized in the BMAC and SVF injection protocols. Complications were reported in 50% of the BMAC studies (knee stiffness, persistent knee swelling) and 67% of the SVF studies (knee swelling, knee pain, positive SVF cultures without symptoms of infection, and bleeding at the abdominal harvest site). Conclusion: A single BMAC or SVF injection into the knee joint of patients with OA resulted in symptomatic improvement at short-term follow-up. However, SVF seemed to be more effective than did BMAC in the reduction of knee pain. There was significant variation in the BMAC and SVF injection preparation techniques used across the studies and a lack of stratification of outcomes based on the radiologic classification of OA. Therefore, these results should be taken with caution.